2020
DOI: 10.1055/s-0039-3401801
|View full text |Cite
|
Sign up to set email alerts
|

Time Has Come for Routine Penicillin Allergy Testing in Obstetrics

Abstract: Objective This study evaluates penicillin allergy during pregnancy to estimate the proportion that could benefit from penicillin allergy testing. Study Design Retrospective cohort study of women with penicillin allergy that delivered from January 1, 2018 to December 31, 2018. Results Among 6,321 deliveries, 446 (7%) were identified with penicillin allergy. Nine percent (41/446) had no documentation of allergy severity. Allergies associated with intolerance, low, moderate, or high risk of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Another recent retrospective study of 447 women with a reported penicillin allergy stratified patient allergies to undocumented, low, moderate or high risk. 1 The authors found that 81% of women were candidates for penicillin allergy testing. 1 The implementation of penicillin allergy testing in pregnancy would affect a large proportion of reported allergic women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another recent retrospective study of 447 women with a reported penicillin allergy stratified patient allergies to undocumented, low, moderate or high risk. 1 The authors found that 81% of women were candidates for penicillin allergy testing. 1 The implementation of penicillin allergy testing in pregnancy would affect a large proportion of reported allergic women.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The authors found that 81% of women were candidates for penicillin allergy testing. 1 The implementation of penicillin allergy testing in pregnancy would affect a large proportion of reported allergic women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 81% of reportedly allergic women would be eligible for allergy delabeling after stratifying based on their history and perceived risk. 19 Delabeling may be challenging based on the limited history evaluation reportedly performed by obstetric providers in our survey. Additionally, the majority of respondents did not feel fully prepared to prescribe antibiotics to pregnant patients with even less feeling "very prepared" after education, however, more individuals feeling somewhat prepared.…”
Section: Accepted Manuscriptmentioning
confidence: 99%